Economic Analysis of Deep Peak-Shaving Reform of 600MW Thermal Power Unit in Beijing-Tianjin-Tangshan Power Grid. Issue 1 (February 2021) - Guo, Yujie; Tian, Xueqin; Xu, Tong; Wang, Xinlei
Abstract: Promoting deep peak-shaving reform to excavate the peak-shaving potential of thermal power unit is an important way to solve the renewable energy consumption contradiction in Beijing-Tianjin-Tangshan power grid, which is restricted by the rationality of deep peak-shaving revenue. Based on the peak-regulation auxiliary service in Beijing-Tianjin-Tangshan power grid, this paper analyses the economy of deep peak-shaving reform of a 600MW thermal power unit and the effect of peak-shaving demand and coal price, providing reference for the operation management of thermal power units.